Arylboronic Acids and their Myriad of Applications Beyond Organic Synthesis. Issue 31 (25th May 2020) - Hiller, Noemi de Jesus; do Amaral e Silva, Nayane Abreu; Tavares, Thais Apolinário; Faria, Robson Xavier; Eberlin, Marcos Nogueira; de Luna Martins, Daniela
Abstract : Boron organometallic compounds are mainly known for their great value in organic synthesis to construct biaryls in Suzuki couplings, for arylations of olefins, for C–S, C–O, and C–N couplings or as organometallic catalysts. Herein, using arylboronic acids (Ar‐B(OH)2 ) as a illustrative case, we review the applications of these highly versatile molecules which expands much beyond their commonly perceived uses. Seeing primarily as "mere" intermediates in organic synthesis and organometallic catalysis, this review shows many examples of their uses in other areas of chemistry and seeks therefore to contribute to awaken scientists to the wide range of new possibilities that have been opened to boronorganic compounds, which have acted indeed as very versatile and attractive chemicals with much desirable characteristics such as safety, stability, and chemical diversity. Because the chemistry of boronic acids is extremely wide, we focused on arylboronic acids, which represent an illustrative case since their properties can be modulated by the nature of the ring or the ring substituents. Illustrative applications in analytical chemistry such as in chromatography and electrophoresis, as well as in probes to detect and quantify a variety of different chemical species and as derivatizing agents to determine enantiomeric excess in nuclear magnetic resonance spectroscopy are also given. Applications of arylboronic acids in areas as diverse as the chemistry of new materials to develop supramolecular architectures and in medical chemistry, including diagnostics, neutron capture therapy and as pharmaceutical drugs are also reviewed. Abstract : Using arylboronic acids (Ar‐B(OH)2 ) as an illustrative case of boronorganic compounds, the applications of these highly versatile molecules which expands much beyond their commonly perceived uses are reviewed.